+0  
 
0
80
3
avatar+8 

Suppose \(f\) is a polynomial such that \(f(0)=47\)\(f(1)=32\)\(f(2)=-13\), and \(f(3)=16 \). What is the sum of the coefficients of \(f\)?

 Mar 6, 2021
 #1
avatar
0

We exclude the constant term, so the sum of the coefficients is f(1) - f(0) = 32 - 47 = -15.

 Mar 6, 2021
 #2
avatar+8 
+1

sorry incorrect @CPhill plz help ur the best

nicpro1  Mar 6, 2021
edited by nicpro1  Mar 6, 2021
 #3
avatar+8 
+1

its 32 nvm

 Mar 6, 2021

52 Online Users

avatar
avatar
avatar
avatar
avatar